BEDA PENGARUH PEMBERIAN CLOSE KINETIC CHAIN DENGAN ISOMETRIC QUADRICEPS TERHADAP PENINGKATAN KEMAMPUAN FUNGSIONAL OSTEOARTRITIS LUTUT - Dwi Arwita Surya; Setiawan; Sugiono (Jurusan Fisioterapi Poltekkes Kemenkes Surakarta, 2024)
Background : Problems in knee osteoarthritis sufferers include pain in the knee, limited range of motion (LGS) in the knee, decreased muscle strength, stiffness , impaired joint stability, and decreased functional ability. Osteoarthritis sufferers generally experience functional impairment or decreased functional abilities such as getting up from sitting, squatting, going up and down stairs or other activities that put stress on the knees. Objective : To determine the effect of close kinetic chain training and isometric quadriceps muscle training on increasing functional ability in sufferers of knee osteoarthritis . Method : The type of research used is quasi experimental , namely two group pre and post test design . Subjects : The subjects of this research were 20 patients with osteoarthritis knee pain who were divided into 2 groups so that each group consisted of 10 people. The intervention was carried out twice a week for 4 weeks. The measuring tool for this research uses the Womac scale . Measurements were carried out at the beginning and end of the study. Results : Post test difference between group I and group II using an unpaired t-test ( independent sample t-test ), obtained a p value of 0.003 (p0.05), which means there is a difference. It can be concluded that there is a significant difference between the close kinetic chain training group and the isometric quadriceps muscle training group . The value obtained from the different mean test in group I (difference 3.4) is greater than group II (difference 2.6), so in group I, namely the close kinetic chain, has a more effective influence on improving the ability of functional activities in sufferers of knee osteoarthritis . Conclusion : There is a difference in the effect between close kinetic chain training and isometric quadriceps training on increasing functional ability in sufferers of knee osteoarthritis .